Utilization of Fermented Banana Stems Kepok Waste Using Eco enzymes on Carcass Percentage of Local Male Sheep - Y.S Panjaitan; A. Sadeli; P. Patriani; I. Siburian (Jurnal Peternakan Integratif, 2023)
The cost of feed is the largest proportion in raising livestock. This study aims to determine the effect of the administration of fermented kepok banana stem waste using eco enzymes as an alternative feed on local sheep. This research was conducted at Alvino Farm in September - December 2022. The design used was completely randomized (RAL) with four treatments and five replications so that 20 experimental units were obtained. The sheep used were 20 local sheep with an initial weight of 19.65 ± 1 kg. The treatments given were P0 (80% field grass + 20% concentrate without fermented banana stems), P1 (70% field grass + 20% concentrate + 10% fermented banana stems), P2 (60% field grass + 20% concentrate + 20 % fermented banana stems), and P3 (50% field grass + 20% concentrate + 30% fermented banana stems). The parameters studied were final weight, slaughter weight, empty body weight, carcass weight, and carcass percentage. The results showed that the provision of fermented banana stems up to a level of 30% improve empty body weight. However, it do not improve final weight, slaughter weight, carcass weight, and carcass percentage.